2008
DOI: 10.1002/cne.21592
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular glutamate transporters define two sets of glutamatergic afferents to the somatosensory thalamus and two thalamocortical projections in the mouse

Abstract: The ventral posterior nucleus of the thalamus (VP) receives two major sets of excitatory inputs, one from the ascending somatosensory pathways originating in the dorsal horn, dorsal column nuclei, and trigeminal nuclei, and the other originating from the cerebral cortex. Both systems use glutamate as neurotransmitter, as do the thalamocortical axons relaying somatosensory information from the VP to the primary somatosensory cortex (SI). The synapses formed by these projection systems differ anatomically, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
130
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(152 citation statements)
references
References 82 publications
21
130
1
Order By: Relevance
“…This expression pattern is consistent with a VGLUT2 protein-dense terminal field found within thalamic recipient layers of sensory cortex (Kaneko et al, 2002;Nahmani and Erisir, 2005;Graziano et al, 2008;Hackett and de la Mothe, 2009). However, recent studies find that type 1 glutamate transporter (VGLUT1) mRNA is coexpressed with VGLUT2 mRNA in a subset of MGBv neurons in rodents (Barroso-Chinea et al, 2007;.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…This expression pattern is consistent with a VGLUT2 protein-dense terminal field found within thalamic recipient layers of sensory cortex (Kaneko et al, 2002;Nahmani and Erisir, 2005;Graziano et al, 2008;Hackett and de la Mothe, 2009). However, recent studies find that type 1 glutamate transporter (VGLUT1) mRNA is coexpressed with VGLUT2 mRNA in a subset of MGBv neurons in rodents (Barroso-Chinea et al, 2007;.…”
Section: Introductionsupporting
confidence: 80%
“…2D,G). This resembles that seen in other auditory and sensory cortices (Nahmani and Erisir, 2005;Graziano et al, 2008;Hackett and de la Mothe, 2009) and suggests that VGLUT2 protein expression alone does not readily distinguish the thalamocortical pathways to frequency-organized fields, A1 versus cSRAF.…”
Section: Resultsmentioning
confidence: 55%
“…Recent studies have shown that the refinement of the climbing fiberPurkinje cell connection in the cerebellum is associated with pruning of somatic innervation (33). Synaptic terminals of Pr5 axons in the VPm selectively express vesicular glutamate transporter 2 (VGluT2), whereas those of corticothalamic axons express only VGluT1 (34). This allowed us to visualize Pr5 axon terminals by using VGluT2 immunostaining.…”
Section: Resultsmentioning
confidence: 99%
“…Mapping of lemniscal thalamic boutons shows meaningful remodeling of terminal fields in reeler barrel cortex We took advantage of the recently shown specificity of vGluT2-antibodies to reveal the distribution of lemniscal thalamic boutons in the sensory neocortex (Graziano et al, 2008). In wild type, the clear modular pattern of termination in layer IV was reminiscent of barrels, which receive the densest innervation from the VPM (Fig.…”
Section: Colocalization Of C-fos and Laminar Markersmentioning
confidence: 99%